The effects of deep breathing on the mental toughness of athletes in Puchong Fuerza football club - Fakrul Hazely Ismail; Zulakbal Abd Karim; Nuraliah Amani Rozali; Ramesh Ram Ramalu (IP Iermakov S.S., 2022)
Background and Study Aim.  A group of psychological traits that are essential to achieving peak performance are referred to collectively as mental toughness. One of the most significant  psychological traits linked to sports success, according to athletes, coaches, and sport psychologists, is mental toughness. This study aims to identify the effects of deep breathing on the mental toughness of athletes in Puchong Fuerza Football Club who played in M3 Football League, the Malaysia's third-tier football league. Material and Methods. The research was conducted experimentally with two sessions which include pre-test and post-test. Mental Toughness Questionnaire 48 (MTQ48) and deep breathing techniques were used in this research. Data findings were analyzed to answer the research questions and null hypothesis. Hypothesis testing was used, and inferential statistics analyzed the data. Paired sample t-test was used to identify the effects of deep breathing techniques on mental toughness scores in pre-test and post-test. Results.  The analysis results showed that data on mental toughness was negative. It proved by the mean score difference of the pre-test and post-test, in which there were increments of mental toughness score after applying deep breathing technique. Meanwhile, there was a significant difference in mean scores between players toward their mental toughness based on pre-test and post-test results. Conclusions. Therefore, the deep breathing technique has relations with performance and psychological outcomes and can be use as a pre-match mental preparation. It is suggested that coaches and athletes may include the deep breathing technique in training program. The players need to undergo psychological skill training such as deep breathing technique to improve their mental toughness and to ensure that anxiety is at an optimal level in order to achieve excellent performance in competitions.